Mediterranean refugee traffic: main routes and problems of control - Vasily D. Ostanin-Golovnya; Anna A. Pavliukova (Научно-аналитический вестник Института Европы РАН)
The article analyzes the Mediterranean routes used by refugees from the Middle East and North Africa (MENA) on their way to the European Union. The authors cite data from reports by the United Nations High Commissioner for Refugees, the United Nations Relief and Works Agency for Palestine Refugees in the Near East, the World Organization against Torture, and a number of other international institutions. The relevance of this area of research is due to the fact that today there are about 118.3 million refugees and internally displaced persons in the world, and their main countries of origin are in the MENA regions, including Afghanistan and Somalia. The article provides up-to-date information for 2022–2023, including data on the three most important refugee trafficking routes between MENA and Europe in the Mediterranean. The most popular of them is the Central Mediterranean route, which runs from Tunisia and Libya, then the Western Mediterranean route – from Morocco and Algeria. In addition, the West African route has recently become more popular due to the strengthening of the coast guard on the two previously mentioned routes. It is used to get to the Canary Islands. The authors also cited forecasts from the European Union Agency for the Security of its External Borders for 2023–2024, which say that the pandemic and the economic crisis have affected migration flows, which will grow in the near future. But, on the other hand, the European Union is actively developing cooperation with North African countries to prevent illegal migration, but different methods are used for this: strengthening the coast guard, allocating funds from the EU budget and individual countries «to combat illegal migration», developing a circular migration program aimed at attracting migrants for seasonal work.